Immersion into the Datascape: Ryoji Ikeda's Data Composition in Screen-Centric Audiovisual Installation and Its Embodied Experience. - Lee, Joo Yun (Afterimage, 2024)
This essay examines an immersive audiovisual installation created by Paris-based Japanese composer and visual artist Ryoji Ikeda, who conjures micro/macro datascapes and their embodied experience, opening a new realm at the intersection of art and data, or data art. Ikeda interfaces his sound compositions with light, visuals, numerical data, and data visualization, bringing audible/inaudible and visible/invisible data into viewers' fields of perception. Focusing on his exhibition the transfinite at the Park Avenue Armory in New York City in 2011, I examine Ikeda's approach to temporal articulation in forging the viewer's spatiotemporal immersion into the datascapes in his signature large-scale screen-centric installation work. Ikeda's data composition—which evolved from his music composition—articulates a multi-substance of data from the infinitesimal to the infinite according to sonic media's micro-temporality, formulating a new sensibility of our world enmeshed in unfathomable data at the threshold of the viewer's perception. Given that Ikeda's body of art is integral to his music, I trace the expansion of the arc of his work from music to visual art, discussing his composition of glitch microsound and his early sound-light installation spectra II (2002). Finally, I highlight that Ikeda's screen-centric installations, stemming from his audiovisual performances and his association with the Japanese experimental collective Dumb Type's intermedia production, have shaped a new kind of installation art with a distinct temporal dimension, immersing viewers into the constantly instantiated presence of datascapes rather than into the images on the screen as the direct representation of reality.